ESG AND ORAGANIZATINAL VALUE - Popova Lyudmila; Kamilova M. H. (Journals Park Publishing, 2026)
The article examines how ESG factors are linked to a company’s value. While many studies have explores how ESG perfoprmance and ESG disclosure remains understudied. The findings show that stakeholders consider both a companyu’s ESG achievements and the transparency of its reporting when evaluating its value. Strong ESG performance increases market value, whereas ESF weaknesses reduce it. ESG disclosure on its own may lower firm value. MOreover, extensive ESG reporting weaknes the positive effect of storng ESG performance but softens the negative impact of ESG shortcomings. For firms with strong ESG results, putting too much emphasis on ESG issues can harm their value, as investors may interpret excessive ESG focus as inefficient use of resorces.
Keywords: ESG, SG, correlation, the value of the oragization